2013
DOI: 10.1016/j.poly.2013.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide oxidation by O2: Synthesis, structure and reactivity of novel sulfide-incorporated Fe(II) bis(imino)pyridine complexes

Abstract: The unsymmetrical iron(II) bis(imino)pyridine complexes [FeII(LN3SMe)(H2O)3](OTf)2 (1), and [FeII(LN3SMe)Cl2] (2) were synthesized and their reactivity with O2 was examined. Complexes 1 and 2 were characterized by single crystal X-ray crystallography, LDI-MS, 1H-NMR and elemental analysis. The LN3SMe ligand was designed to incorporate a single sulfide donor and relies on the bis(imino)pyridine scaffold. This scaffold was selected for its ease of synthesis and its well-precedented ability to stabilize Fe(II) io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…Carboxylate-derived Fe–O distances have a similar range but depend on the binding mode of the carboxylate ligand (i.e., monodentate vs bidentate or terminal vs bridging). Additionally, in synthetic iron­(II) complexes, Fe II –OH 2 distances can range from 2.04 to 2.16 Å, consistent with this assignment. The Fe–O/N scatterer at 1.97 Å is assigned to the hydroxo bridge between the metal centers, as synthetic (μ-hydroxo)­diferrous complexes have Fe II –μ-OH distances as short as 1.97 Å. This assignment would agree with the single atom bridge observed in the crystal structure of WT R and give rise to a diiron­(II) active site with an overall neutral charge. Mössbauer studies of WT R reveal a diiron­(II) center with weak antiferromagnetic coupling ( J ∼ 12 cm –1 ) .…”
Section: Resultssupporting
confidence: 72%
“…Carboxylate-derived Fe–O distances have a similar range but depend on the binding mode of the carboxylate ligand (i.e., monodentate vs bidentate or terminal vs bridging). Additionally, in synthetic iron­(II) complexes, Fe II –OH 2 distances can range from 2.04 to 2.16 Å, consistent with this assignment. The Fe–O/N scatterer at 1.97 Å is assigned to the hydroxo bridge between the metal centers, as synthetic (μ-hydroxo)­diferrous complexes have Fe II –μ-OH distances as short as 1.97 Å. This assignment would agree with the single atom bridge observed in the crystal structure of WT R and give rise to a diiron­(II) active site with an overall neutral charge. Mössbauer studies of WT R reveal a diiron­(II) center with weak antiferromagnetic coupling ( J ∼ 12 cm –1 ) .…”
Section: Resultssupporting
confidence: 72%
“…33,34 It must be stressed that the formation of the Schiff base is reversible, which imposes certain constraints on the synthesis. 35 2,6-Dimethylpyridine was also used as a starting material to synthesize dibenzoylpyridine, which was subsequently condensed with the aniline derivative to yield the diiminopyridine incorporating the phenyl rings attached to the imine carbon atoms (see Figure 4a). 21 Alternatively, dibenzoylpyridine was also obtained in a Friedel−Crafts acylation of benzene with 2,6dicarbonylpyridine dichloride.…”
Section: Distinct Synthetic Methodsmentioning
confidence: 99%
“…[165] Methylation of the thiolate moiety to the methyl sulfide led to the formation of sulfoxide ands ulfone in lieu of sulfonic acid. [166] Substitution of triflate counter anion with different pyridines impacted the reactivity only modestly. [165] Later,i n2 011, [167] the authors demonstrated that the oxidation does not require the thiolate to be covalently anchored on the ligand.…”
Section: Other Imine-based Iron Complexesmentioning
confidence: 99%